A better effect of cilostazol for reducing in-stent restenosis after femoropopliteal artery stent placement in comparison with ticlopidine - Ikushima I (Dove Medical Press, 2011)
Ichiro Ikushima1, Kazuchika Yonenaga1, Hironao Iwakiri2, Hideki Nagoshi2, Haruhito Kumagai2, Yasuyuki Yamashita31Department of Radiology, 2Department of Cardiology, Miyakonojo Medical Association Hospital, Miyakonojo, Japan; 3Department of Diagnostic Radiology, Faculty of Life Sciences, Kumamoto University, Kumamoto, JapanPurpose: The purpose of this study was to assess the preventive effect of cilostazol on in-stent restenosis in patients after superficial femoral artery (SFA) stent placement.Materials and methods: Of 28 patients with peripheral arterial disease, who had successfully undergone stent implantation, 15 received cilostazol and 13 received ticlopidine. Primary patency rates were retrospectively analyzed by means of Kaplan–Meier survival curves, with differences between the two medication groups compared by log-rank test. A multivariate Cox proportional hazards model was applied to assess the effect of cilostazol versus ticlopidine on primary patency.Results: The cilostazol group had significantly better primary patency rates than the ticlopidine group. Cumulative primary patency rates at 12 and 24 months after stent placement were, respectively, 100% and 75% in the cilostazol group versus 39%and 30% in the ticlopidine group (P = 0.0073, log-rank test). In a multivariate Cox proportional hazards model with adjustment for potentially confounding factors, including history of diabetes, cumulative stent length, and poor runoff, patients receiving cilostazol had significantly reduced risk of restenosis (hazard ratio 5.4; P = 0.042).Conclusion: This retrospective study showed that cilostazol significantly reduces in-stent stenosis after SFA stent placement compared with ticlopidine.Keywords: cilostazol, ticlopidine, stent, primary patency rate, peripheral arterial disease, superficial femoral artery